Synchronization Techniques in "Device to Device- and Vehicle to Vehicle-Enabled" Cellular Networks: A survey. (March 2021) - Abbasi, Mahmoud; Shahraki, Amin; Barzegar, Hamid R.; Pahl, Claus
Abstract: Device-to-Device (D2D) communication is introduced for cellular networks allowing User Equipments (UEs) to communicate directly in close physical proximity. In traditional cellular networks, time synchronization is performed by the network infrastructure equipment to address the challenges of coordinating independent clocks and tasks of UEs to communicate with each other. These challenges are more critical in D2D as the network has no central point to coordinate UEs. The aim of this paper is twofold: (i) reviewing synchronization standards and techniques for D2D-enabled cellular networks and (ii) discussing different scenarios and contemporary cellular network generations. We review the main signals, channels, and entities used by D2D-enabled cellular networks for synchronization procedures in different scenarios. Moreover, we focus on the synchronization in Vehicle-to-Vehicle (V2V) and Vehicle-to-Everything (V2X). Finally, we conduct a literature study on effective proposed synchronization techniques in D2D and vehicular communications to highlight recent advances and provide future directions. Graphical abstract: Highlights: Device-to-Device communication allows a user to communicate directly with other users in its proximity. Network synchronization aims at delivering a standard clock reference to nodes in the network within specific accuracy and stability. D2D synchronization is a compulsory procedure for both public safety applications and proximity discovery. Different scenarios of synchronization in Vehicle-to-Vehicle-enabled cellular networks. Device-to-Device, also known as Proximity Service, is introduced in Release 12 of the Third Generation Partnership Project.